PENGARUH PROSES QUENCHING DAN HEATTREATMENT PADA VELG BESI MOBIL TOYOTA KIJANG LGX - HP, Bambang; Hafid, Achmad; Lufti, Aryananta (PPM Sdirjianbang Akademi Militer, 2023)
Iron precious metals have been used since antiquity, although those with lower melting points, which were used earlier in human history, pure iron are relatively softer but cannot be obtained through smelting. This material hardens and is significantly strengthened by carbon impurities, especially in the smelting process. With a certain proportion of carbon (between 0.002% and 2.1%) it will produce harder steel than pure iron which may reach 1000 times. Iron compounds have many benefits in daily life. Iron has a very high economic value so many people make iron as a business land. Most of the usefulness of iron is in the world of construction. Many material elements are used in the world of iron-based construction because the strength of the modified iron is more beneficial and useful. This is because the cast properties of this alloy are classified as good, in addition to corrosion resistance and easy to process machines, alloy types this is widely used in the automotive industry object used is the LGX Toyota kijang alloy wheels. In this study, to obtain data, several tests were carried out, namely Heat Treatment, Quenching, Aneling, composition testing, and tensile testing. The results showed that the effect of heat treatment and quenching on iron alloy specimens was the increase in the value of hardness and tensile strength values, when compared with non-heat treatment specimens. While the strength of the pulses is not measurable because the specimens are too brittle .